Safety profile of metformin in adolescents with type 2 diabetes: A pharmacovigilance analysis of the FDA Adverse Event Reporting System - Mengsi Peng; Peng Shen; Kyung-In Joung; Kwang Joon Kim (PLoS ONE, 2025)
Background Although metformin is the first-line medicine for type 2 diabetes (T2D), its safety profile in adolescents remains poorly understood. This study seeks to investigate the adverse events linked to metformin use in adolescents diagnosed with T2D. Methods Data from the Food and Drug Administration Adverse Event Reporting System (FAERS), spanning Q1 2004 to Q2 2024, were retrospectively analyzed in this study. Adverse reactions were standardized using the Medical Dictionary for Regulatory Activities, then significant adverse drug reaction signals were identified through disproportionality analysis employing reporting odds ratio (ROR) and information component (IC) methods. Results Of 17,956,653 FAERS reports, 80,187 involved metformin, including 973 in adolescents (10–19 years), with 174 cases were identified with a T2D indication. Analysis at the system organ class level revealed that congenital, familial, and genetic disorders [ROR: 8.8 (4.0, 19.3); IC: 2.2 (1.1, 2.9)] and pregnancy conditions [ROR: 4.9 (2.5, 9.5); IC: 1.8 (0.8, 2.5)] showed the most significant signals. At the preferred term (PT) level, three signals were identified across all sexes and subgroups: treatment noncompliance [ROR: overall 4.14 (2.44, 7.02), male 4.27 (2.00, 9.12), and female 4.65 (2.22, 9.74); IC: overall 1.67 (0.88, 2.22), male 1.60 (0.46, 2.36), and female 1.74 (0.60, 2.50)], lactic acidosis [IC: overall 2.99 (1.91, 3.72), male 2.53 (0.76, 3.61), and female 2.76 (1.34, 3.67)], and gastrointestinal disorder [ROR: overall 13.09 (4.73, 36.23), male 54.33 (6.05, 487.96), female 5.34 (1.10, 25.84)]. Neurological disorders were observed only in males, while pregnancy-related adverse effects and renal disorders occurred exclusively in females. Additionally, the study identified potential new signals not documented in metformin labeling, including areflexia, muscle weakness, ataxia, decreased vibratory sense, rhabdomyolysis, substance use, and axillary pain. Conclusion The study reveals a complex safety profile of metformin in adolescents with T2D, warranting further research to confirm risks.